Infl uence of indole-3-butyric acid and triazole compounds on the growth and antioxidant constituents in Ashwagandha (Withania somnifera L.) Dunal - Ramalingam Sridharan, Panneerselvam Sakthivel (Journal of Medicinal Herbs and Ethnomedicine, 2015)
Withania somnifera (L.) Dunal belongs to the family Solanaceae and commonly known as Ashwagandha, Indian ginseng and winter cherry is major ayurvedic medicinal plant cultivated specifically for its root portion, which has medicinal and nutritional values due the presence of clinically important active compounds such as steroidal lactones, alkaloids, flavonoids, and tannins etc. Ashwagandha root is the medicinal part of the plant and is used in the ayurvedic formulations and pharmaceutical industries. The present study was undertaken to investigate the influence of indole-3-butyric acid (IBA) and triazole compounds viz., triadimefon (TDM) and propiconazole (PCZ) on the growth and non-enzymatic antioxidant content of Ashwagandha. Plants were treated with IBA 2.5 mg/L, TDM 20 mg/L and PCZ 20 mg/L separately by soil drenching on 50, 90, 130 days after sowing (DAS). Plants were analyzed on 60, 100 and 140 DAS and it’s parameters such as shoot length, internodal length, number of leaves, total leaf area, fresh and dry weight of shoot, root length, root diameter, number of roots, fresh and dry weight of root, ascorbic acid (AA), α-tocopherol (α-toc) and total phenol (TP) contents were determined. It was observed that shoot length, internodal length, the number of leaves, total leaf area, fresh and dry weight of shoot decreased, but the root length, root diameter, number of roots fresh and dry weight of roots were increased higher level. Likewise, the non-enzymatic antioxidants constituents such as AA, α-toc and TP contents were also increased by TDM and PCZ treatments. But IBA treatment increased all the parameters studied. Among the treatments, triazole showed beneficial growth by increasing the biomass of root system antioxidant constituents when compared to IBA treatment. This finding suggested that the triazole compounds showed a great significant for the cultivation of medicinally important root crops, which is helpful to meet the needs of root production by enhancing antioxidant constituents in Ashwagandha.